The Potential for Cancer Immunotherapy in Targeting Surgery-Induced Natural Killer Cell Dysfunction - Market, Marisa (Cancers (Basel), 2018)
Natural Killer (NK) cells are granular lymphocytes of the innate immune system that are able to recognize and kill tumor cells without undergoing clonal selection. Discovered over 40 years ago, they have since been recognized to possess both cytotoxic and cytokine-producing effector functions. Following trauma, NK cells are suppressed and their effector functions are impaired. This is especially important for cancer patients undergoing the removal of solid tumors, as surgery has shown to contribute to the development of metastasis and cancer recurrence postoperatively. We have recently shown that NK cells are critical mediators in the formation of metastasis after surgery. While research into the mechanism(s) responsible for NK cell dysfunction is ongoing, knowledge of these mechanisms will pave the way for perioperative therapeutics with the potential to improve cancer outcomes by reversing NK cell dysfunction. This review will discuss mechanisms of suppression in the postoperative environment, including hypercoagulability, suppressive soluble factors, the expansion of suppressive cell populations, and how this affects NK cell biology, including modulation of cell surface receptors, the potential for anergy, and immunosuppressive NK cell functions. This review will also outline potential immunotherapies to reverse postoperative NK dysfunction, with the goal of preventing surgery-induced metastasis.